2016
DOI: 10.1002/cmdc.201600315
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the in vitro Anticancer Effects of Diruthenium‐1

Abstract: The in vitro anticancer activity of the dinuclear trithiolato-bridged arene ruthenium complex diruthenium-1 (DiRu-1) was evaluated against a panel of human cancer cell lines used as in vitro models for hepatocellular carcinoma (HepG2 cells), estrogen-responsive breast adenocarcinoma (MCF-7 cells), and triple-negative breast adenocarcinoma (MDA-MB-231 cells). DiRu-1 is highly cytotoxic to these cell lines, demonstrating half-maximal inhibitory concentrations (IC ) in the low-nanomolar range (77±1.4 to 268.2±4.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 102 publications
(244 reference statements)
4
35
0
Order By: Relevance
“…Nevertheless, the existence of other non-apoptotic nor necrotic cell death pathways, triggered upon exposure to ruthenium-containing nanoaggregates we have documented in breast cancer models, needs further and more targeted studies. According to our previous findings24 and to recent literature reports3652, it cannot be excluded that the simultaneous activation of different mechanisms of cell death can be caused by multiple potential interactions at the subcellular/molecular level, both nuclear and cytosolic. Nevertheless, the activation of multiple death pathways by metal-based chemotherapeutics in aggressive cancer diseases with limited treatment options is a largely desired goal, in order to possibly restrict the onset of chemoresistance as well as to efficiently counteract uncontrolled proliferation.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, the existence of other non-apoptotic nor necrotic cell death pathways, triggered upon exposure to ruthenium-containing nanoaggregates we have documented in breast cancer models, needs further and more targeted studies. According to our previous findings24 and to recent literature reports3652, it cannot be excluded that the simultaneous activation of different mechanisms of cell death can be caused by multiple potential interactions at the subcellular/molecular level, both nuclear and cytosolic. Nevertheless, the activation of multiple death pathways by metal-based chemotherapeutics in aggressive cancer diseases with limited treatment options is a largely desired goal, in order to possibly restrict the onset of chemoresistance as well as to efficiently counteract uncontrolled proliferation.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, classical chemotherapy is currently the only drug-based option in the therapeutic armamentarium, and metal-based chemotherapy is also emerging as an upcoming treatment modality especially in TNBC35. Although new types of ruthenium complexes with superior anticancer activity in vitro have been meanwhile reported36, the induction of comparable or even greater cytotoxic effects than cisplatin have been herein confirmed for nucleolipidic Ru(III) formulations. Then, aiming at an in-depth investigation of their mode of action, we have shown that amphiphilic ruthenium complexes, properly delivered by suitable nano-systems, are able to kill cancer cells by activating specific apoptotic processes, coupled in some cases to cellular autophagy.…”
Section: Discussionmentioning
confidence: 94%
“…It has been reported that DiRu‐1 triggers the production of ROS in MCF‐7 cells . Therefore, oxidative stress was evaluated by measuring intracellular ROS in cells incubated with DiRu‐1 or DiRu‐1‐encapsulated AFt for various periods of time (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
“…The most active member of this family is [(η 6 ‐ p ‐Me‐C 6 H 4 i Pr) 2 Ru 2 (μ 2 ‐S‐ p ‐C 6 H 4 t Bu) 3 ]Cl, termed diruthenium‐1 or DiRu‐1 (Figure ) . This compound is very toxic in vitro toward hepatocellular carcinoma (HepG2 cells), estrogen‐responsive breast adenocarcinoma (MCF‐7 cells) and BT549 cells, triple‐negative breast adenocarcinoma (MDA‐MB‐231 cells), human ovarian cancer (A2780 cells), and the cisplatin‐resistant cell line A2780cis, with IC 50 values in the low nanomolar range . Recent in vivo studies, have demonstrated that these complexes have potential as anticancer drugs, especially DiRu‐1, which significantly prolongs the survival of tumor‐bearing mice .…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxic and proapoptotic effects of DiRu-1 were attributed to the increase in intracellular levels of ROS, while the anticancer effect was due to the induction of DNA lesions caused by apoptotic DNA fragmentation and cell-cycle arrest at the G 2 /M checkpoint. 23 In summary, the diverse modes of action of Ru anticancer drugs likely enhanced their anticancer activities and minimized the potential for cancer cells to …”
Section: (Pip)]mentioning
confidence: 99%